Asuhan Keperawatan Pada Pasien Deman Thypoid Di Ruang Muzdalifah Di RS Aisyah Pariaman - Silfi Nugrahini; Linda Marni; Kheniva Diah Anggita; Aulia Asman (CV. ITTC INDONESIA, 2026)
Typhoid fever is a systemic infectious disease caused by Salmonella enterica and remains a major public health problem in developing countries. According to data from the World Health Organization (2023–2024), approximately 20 million cases of typhoid fever occur annually in Asia. In Indonesia, the incidence rate ranges from 350 to 810 cases per 100,000 population. In West Sumatra, 46,142 cases were reported in 2023, with a mortality rate of 1.52%. At Aisyiyah Pariaman Regional Hospital, the number of typhoid fever cases increased by 358 cases during the period of 2023–2025. This case study aimed to provide nursing care for a patient with typhoid fever in the Muzdalifah inpatient ward of Aisyiyah Pariaman Regional Hospital in 2026. The method used was the nursing process, including assessment, nursing diagnosis, intervention, implementation, and evaluation. The assessment of Mr. R, a 33-year-old patient, identified nursing problems consisting of hyperthermia, acute pain, disturbed sleep pattern, and knowledge deficit. After the implementation of nursing care, all nursing problems were resolved, as evidenced by the normalization of body temperature, reduction of abdominal pain, improvement in sleep patterns, and increased patient knowledge regarding the disease. Adherence to treatment, healthy lifestyle practices, proper nutrition, and good personal hygiene are essential to prevent recurrence and improve overall health outcomes.